A study of synthesis and properties of poly‐3‐hydroxybutyrate/diethylene glycol copolymers. (27th April 2016) - Volova, Tatiana; Zhila, Natalia; Kiselev, Evgeniy; Shishatskaya, Ekaterina
Abstract : This study investigates synthesis of poly(3‐hydroxybutyrate)/diethylene glycol copolymers (P3HB/DEG) by Cupriavidus eutrophus B‐10646 cells as related to DEG concentration in the medium and the time when it is added to the culture of cells synthesizing P3HB. The study determines the limits of physiological effect of DEG on C. eutrophus cells, showing that at DEG concentrations above 30 g/L, it inhibits cell growth, decreasing cell concentration and total P3HB/DEG yield and inducing an increase in the degree of saturation of fatty acids in lipids of cell cytoplasmic membrane. A series of copolymers containing different molar fractions of DEG (between 0.13 and 3.0 mol%) have been synthesized and their physicochemical, physical/mechanical, and biological properties have been investigated as related to the chemical composition and proportions of DEG monomers of the polymers. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:1017–1028, 2016